My name is Afrika: Setswana genealogies, trans-atlantic interlocutions, and NOW-time in Keorapetse Kgositsile's life and work - Phalafala, Portia Mahlodi (Department of English Language and Literature, 2017)
South African poet laureate Keorapetse Kgositsile lived in extraordinary times marked by extraordinary challenges and changes. Born in 1938, exactly a decade before the draconian apartheid regime came into power, his life and work emerge from the milieus of British colonial South Africa, apartheid South Africa, civil rights America, anti-apartheid movements, anti-colonial wars in Africa, anti-imperialism in Asia, cold war politics, and the eventual demise of both the Berlin wall and the apartheid regime in South Africa. His poetry responds to these times in illuminating ways. His poetic influences point to his Tswanacentred upbringing, his encounter with Afro-American oral and literary traditions, the styles and poetics of Drum writers, the outpouring of African literature he received from the Makerere conference of Uganda, and anti-colonial critical thinkers from Africa and its diaspora. At age twenty three, post-Sharpeville massacres, he was sent into exile by the leadership of the ANC, and he took with him a corpus of Tswana literature which would in/form his poetic. He readily immersed himself in the oral and written tradition of Afro-America while in exile in the United States of America. His work interweaves the oral and literary traditions of black South Africa and black America, revealing a dynamic and complex relationship between the two geographical sites. Where oral traditions have largely been left out of the broader narrative of modernity, this study demonstrates how oral traditions remain alive and are reinvigorated, providing a resource that is then carried across the Atlantic and renewed in translation, rather than left behind to ossify. Kgositsile's prominent presence in black international periodicals and his collaborations with other diasporic cultural, political and musical figures there show that the relationship between the two geographical sites is more complex than its current positioning of Afro-America as a vanguard on which Africans model themselves. Through a reading of Kgositsile's revolutionary poetry, this study also shows how the indigenous resource base enables him to resolve the agonising temporal and spatial tensions presented by modernity's colonialism. He coins concepts that re-enchant the world through a poetic that fosters a dialogue between past and future, and traditional and modern in a simultaneous present he deems the NOW-time.